2007
DOI: 10.1021/jp070337o
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies of Terrylene in a Supersonic Jet:  Indication of A Dark Electronic State Below the Allowed Transition

Abstract: Jet-cooled terrylene has been studied in helium buffer gas using a pulsed nozzle by means of laser-induced fluorescence. Fluorescence excitation and two-color depletion experiments (resulting in hole burning spectra) are presented. Analysis of the spectra leads to the conclusion that another excited electronic state is present in the vicinity of the allowed 1B1u state. Assuming (according to previous literature suggestions Karabunarliev, S.; Baumgarten, M.; Müllen, K. J. Phys. Chem. A 1998, 102, 7029) that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
10
0
2
Order By: Relevance
“…We studied several single Tr molecules and for all of them we observed these weak lines (with the experimental frequency reading precision of ±2 cm −1 ). Recently, the set of low-frequency modes (with the maxima at 56.6, 106.2, 160.6, and 199.4 cm −1 ) observed in the bulk fluorescence excitation spectrum of Tr in a supersonic jet expansion was attributed to nontotally symmetric vibronic transitions [15]. We postulate the same origin of the mentioned weak lines observed in our experiment.…”
Section: S-91supporting
confidence: 88%
See 1 more Smart Citation
“…We studied several single Tr molecules and for all of them we observed these weak lines (with the experimental frequency reading precision of ±2 cm −1 ). Recently, the set of low-frequency modes (with the maxima at 56.6, 106.2, 160.6, and 199.4 cm −1 ) observed in the bulk fluorescence excitation spectrum of Tr in a supersonic jet expansion was attributed to nontotally symmetric vibronic transitions [15]. We postulate the same origin of the mentioned weak lines observed in our experiment.…”
Section: S-91supporting
confidence: 88%
“…In the spectra detected at high excitation intensity we observed some weak fluorescence excitation lines separated by 38, 67, 97, and 145 cm −1 from the (0,0) origin line. These lines were present in the spectra (measured in appropriate conditions) of the majority of studied single molecules and thus, we propose that they are nontotally symmetric low frequency vibration modes of Tr, recently observed in a supersonic jet expansion [15].…”
Section: Discussionsupporting
confidence: 57%
“…[38] However, the distribution of linewidths is broader than that usually found in single crystals, as shown by the example of DBT in anthracene. For this measurement, the molecule was excited at 569.1 nm, which corresponds to one of the stronger vibrational modes determined from density functional theory (DFT) calculations [39] at 249 cm À1 above the ZPL 00 found at 577.1 nm. Extremely low interactions with low-frequency modes can induce line broadening as a result of dephasing.…”
Section: Capillary Samplementioning
confidence: 99%
“…However, in helium buffer gas, Deperasińska et al found the indication of a dark electronic state below the dipole-allowed electronic state for jet-cooled terrylene. 27 The experimental findings indicate, for oligorylenes, subjected to the environment, that the orderings of the excited states could be changed. Theoretically Karabunarliev et al studied the oligorylenes by using different semiempirical and concluded that for quaterrylene, the optically opaque state becomes the lowest excited state adiabatically, not vertically, while for shorter rylenes, the lowest excited states are dipole-allowed both adiabatically and vertically.…”
Section: Introductionmentioning
confidence: 98%